1999
DOI: 10.1007/s002130051094
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependence of auditory evoked potentials (AEPs) as biological marker for cerebral serotonin levels: effects of tryptophan depletion in healthy subjects

Abstract: The results indicate, in contrast to earlier indirect studies, that the intensity dependence of AEPs is not a specific marker of central serotonergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
58
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 41 publications
8
58
4
Order By: Relevance
“…Reduced serotonin function leads to higher intensity dependence of N1/P2 amplitude and vice versa. However, Dierks et al (1999) were not able to confirm these findings using ATD in healthy subjects. In contract, this study showed that ATD decreases the intensity dependence of N1/P2 amplitudes.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Reduced serotonin function leads to higher intensity dependence of N1/P2 amplitude and vice versa. However, Dierks et al (1999) were not able to confirm these findings using ATD in healthy subjects. In contract, this study showed that ATD decreases the intensity dependence of N1/P2 amplitudes.…”
mentioning
confidence: 65%
“…Several clinical and experimental studies using EEG have suggested that AEPs could be modulated by serotonin (Hegerl and Juckel 1993;Juckel et al 1997;Dierks et al 1999). EEG detects particularly the radial currents generated by activity in the cortical gyri, but also the tangential ones in the sulci.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, acute depletion of serotonin in healthy adults during administration of tryptophan did not alter LDAEP (Debener et al, 2002;Dierks et al, 1999;O'Neill et al, 2008b).…”
Section: Auditory Evoked Potentials and Treatment Responsementioning
confidence: 81%